DYNAMICS OF INTERFAITH COMMUNICATION IN SEGREGATED COMMUNITIES - Alhamuddin; Alifuddin , Muhammad (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2024)
Abstract This study aimed to analyze interfaith communication between Muslims in Aoma and Christians in Ambesakoa, focusing on whether the in-group/out-group dichotomy acted as a barrier and identifying factors that fostered mindful communication. Employing a descriptive phenomenological approach, data were collected through semi-structured interviews and participant observation. Instruments included interview guides and field notes. Thematic analysis of the data revealed the following findings: Firstly, communication occurred nominally but with moderate intensity, shaped by long-term acquaintance and familial ties, and influenced by segregated living environments and individual busyness. Secondly, social interactions transcend primordial boundaries, avoiding stereotypes and prejudices, thereby promoting mindful communication. Thirdly, both communities fostered mindful interfaith communication driven by nationalism, shared family lines, and adherence to kalosara values. This study underscored the importance of inclusive education and cultural values in enhancing interfaith communication in segregated societies. It suggests that promoting deeper understanding and respect across religious divides can mitigate barriers created by in-group/out-group dynamics. By acknowledging and fostering these factors, societies can cultivate environments conducive to harmonious interfaith relations. This research contributes to the broader discourse on interfaith dialogue, highlighting practical strategies for promoting mutual respect and understanding in culturally diverse communities. Abstrak Studi ini bertujuan untuk menganalisis komunikasi lintas agama antara Muslim di Aoma dan Kristen di Ambesakoa, dengan fokus pada apakah dikotomi dalam kelompok/luar kelompok bertindak sebagai penghalang dan mengidentifikasi faktor-faktor yang mendorong komunikasi yang penuh perhatian. Dengan menggunakan pendekatan deskriptif fenomenologis, data dikumpulkan melalui wawancara semi-struktural dan observasi partisipan. Instrumen yang digunakan meliputi panduan wawancara dan catatan lapangan. Analisis tematik dari data mengungkapkan temuan sebagai berikut: Pertama, komunikasi terjadi secara nominal namun dengan intensitas moderat, dipengaruhi oleh kenalan jangka panjang dan ikatan keluarga, serta dipengaruhi oleh lingkungan hidup yang terpisah dan kesibukan individual. Kedua, interaksi sosial melampaui batas-batas primordial, menghindari stereotip dan prasangka, sehingga mendorong komunikasi yang penuh perhatian. Ketiga, kedua komunitas mempromosikan komunikasi lintas agama yang penuh perhatian didorong oleh nasionalisme, garis keturunan bersama, dan nilai-nilai kalosara. Studi ini menekankan pentingnya pendidikan inklusif dan nilai-nilai budaya dalam meningkatkan komunikasi lintas agama di masyarakat yang terpisah. Studi ini juga menyarankan bahwa mempromosikan pemahaman yang lebih dalam dan saling menghormati di antara perbedaan agama dapat mengurangi hambatan yang diciptakan oleh dinamika kelompok dalam/luar kelompok. Dengan mengakui dan mengembangkan faktor-faktor ini, masyarakat dapat menciptakan lingkungan yang mendukung hubungan lintas agama yang harmonis. Penelitian ini memberikan kontribusi pada diskursus lebih luas mengenai dialog lintas agama, dengan menyoroti strategi praktis untuk mempromosikan saling menghormati dan pemahaman dalam komunitas yang beragam budaya.